Anti-inflammatory Effects of Olive Oil and Its Components. Prospects of Application in the Treatment of Inflammatory Bowel Diseases - Anatoly I. Khavkin; Andrew V. Nalyotov; Maria A. Matsynina (Union of pediatricians of Russia, 2024)
In recent years, there has been a significant increase in the prevalence of inflammatory bowel diseases. Despite the significant progress made in the instrumental diagnosis of this group of diseases, their treatment in most cases remains formalized, based on fairly strict schemes. In this context, an urgent area of modern research is to study the effectiveness of the use of diet therapy and certain foods in order to modulate the activity of the inflammatory process, which allows avoiding adverse reactions of immunosuppressive, including immunobiological, therapy. Adherence to the Mediterranean diet has proven its effectiveness in the treatment of chronic non-infectious diseases. Recent studies have also established its benefits in the treatment of inflammatory bowel diseases. Recent studies have also established its benefits in the treatment of inflammatory bowel diseases. This article will present the results of modern research on the effect of the use of olive oil and its components on the course of inflammatory processes in the intestine. A number of studies conducted in vitro and in animal models have revealed the mechanisms by which olive oil and its components have a positive effect on the course of inflammation in the intestinal wall through anti-inflammatory, antioxidant, immunomodulatory and antitumor effects. Few clinical studies conducted on patients with inflammatory bowel diseases have shown the possibility of using diet therapy with the addition of olive oil in this group of patients as an additional treatment.